Induced Hyperfine Field in Doped Chalcopyrite Compounds Cu(In1-xAx)S2 (A = V and Cr) (Dhaka University Journal of Science, 2022)
Hyperfine field and electronic states of doped chalcopyrite compounds Cu(In1-xAx)S2 with A = V and Cr are calculated by Korringa- Kohn-Rostoker Green’s function method, where x denotes the concentration of A atoms. The V and Cr doped compounds are ferromagnetically stable in terms of energy minimization and their electronic states are half metallic. The hyperfine fields in the stable ferromagnetic (FM) state are calculated with their valence and core contributions. In addition, site preference local magnetic moments are calculated for the FM and disordered spin moment (DSM) states. Density of states (DOS) exhibit the spintronic property of half metallicity. The local core and valence field polarizations are found in the doped chalcopyrite systems, where the s-orbital hybridization with the local d-shell is explained in terms of some exchange mechanisms.Dhaka Univ. J. Sci. 69(3): 149-153, 2022 (June)